Biomechanical evaluation of two different types of interbody cages in posterior lumbar interbody fusion - Muhammad Hazli, Mazlan; Todo, Mitsugu; Ida Laila, Ahmad; Takano, Hiromitsu; Yonezawa, Ikuho; Abdul Halim, Abdullah; Muhammad Hilmi, Jalil; Nur Dalilah Diyana, Nordin (The World Academy of Research in Science and Engineering, 2020)
Posterior lumbar interbody fusion (PLIF) related complications such as cage instability, cage subsidence and pedicle screws loosening are among the most prevalent cases reported postoperatively. These conditions are highly related to mechanical factors (PLIF design and material), patient health condition as well as activities conducted by the patient after undergone the surgery. Latest advancement on PLIF technology has created a new technique that allows the application of unilateral cage insertion in an oblique orientation. This solution has potentially overcome the problem related to an unintended mechanical and clinical shortcoming, provided that a bilateral posterior instrumentation (PI) is instrumented to the construct and the cage is fabricated from a material that is closely imitate the modulus elasticity of the cortical bone. In order to prove these statements, an image based finite element analysis (FEA) was conducted to assess the phenomena of cage subsidence and screw loosening by examining the stress profile on the cage construct and the vertebral bodies. Obliquely-placed unilateral PLIF with PI showed the most promising results. It showed the most minimal stress distortion at cage-endplate and pedicle screw-bone interface. In conclusion, the selection of a biocompatible cage material is the most crucial factors that has to be considered in achieving biomechanical superiority in PLIF surgery.